2019
DOI: 10.1186/s40795-019-0275-x
|View full text |Cite
|
Sign up to set email alerts
|

Current status of education and research on public health nutrition in Japan: comparison with South Korea, Taiwan, and mainland China

Abstract: Background: Although the importance of capacity building for public health nutrition (PHN) has been increasing globally, reports on the current status of training programs for PHN in East-Asia including Japan are limited. The aim of this study was to compare the current status of education and research activities in the field of PHN in Japan with those in South Korea, Taiwan, and mainland China. Methods: Necessary information was collected by internet search and telephone inquiry. Collection focused on the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Due to the different political backgrounds, economic policies, cultures, and medical health levels between Taiwan and mainland China, the Taiwan version of the DPET could not be used directly. 31 Moreover, the Taiwan version retains the entries for the response to biological terrorism, which are the task of the Chinese Center for Disease Control and Prevention (CDC) in mainland China, not the task of emergency nurses. Therefore, we adjusted the DPET again.…”
Section: Mainland China Version Of the Disaster Preparedness Evaluati...mentioning
confidence: 99%
“…Due to the different political backgrounds, economic policies, cultures, and medical health levels between Taiwan and mainland China, the Taiwan version of the DPET could not be used directly. 31 Moreover, the Taiwan version retains the entries for the response to biological terrorism, which are the task of the Chinese Center for Disease Control and Prevention (CDC) in mainland China, not the task of emergency nurses. Therefore, we adjusted the DPET again.…”
Section: Mainland China Version Of the Disaster Preparedness Evaluati...mentioning
confidence: 99%
“…In Japan, 58 % of books written by registered dietitians cited any references, but none cited systematic reviews. A previous study suggested that institutions with public health nutrition programmes may not be active in research related to public health nutrition in Japan (57) . This situation may have led to the lack of citation of systematic reviews in Japanese books written by registered dietitians.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this is unknown, but such information may be an expression of food-related philosophy [29] or daily activities (such as family cooking) [28]. Ultimately, these phenomena might be attributable to the inadequate nature of training courses, research centers, and academia in the field of public health nutrition in Japan [37]. Therefore, empirical data on this point are urgently needed.…”
Section: Comparison With Prior Workmentioning
confidence: 99%